Financial liberalisation and sustained interest differentials - Bernhard Fischer (Intereconomics, 1993)
In the last decade, many of the more advanced developing countries in Latin America and Asia have deregulated and opened up their financial markets. What impact has this had on the efficiency of the financial sector? How can the existence of sustained interest differentials be explained?
Keywords: 330; Development Strategy